Environmental Conditions of the City in which Teachers Serve and their Organizational Commitment Perception Levels. (1st April 2016) - Toytok, Esef Hakan; Korkmaz, Mehmet; Anik, Sabri
Abstract: This paper aimed to reveal how environmental conditions influence organizational commitment. The study group consisted of teachers who serve in central Sirnak city. The paper is a mixed model and it utilized the descriptive survey model, which is a quantitative research method, for measuring the organizational commitment level of teachers, and descriptive analysis, as a qualitative study method, for finding out the influence of environmental factors. It was concluded based on the results obtained from the paper that the organizational commitment levels of teachers were low. It can be said that the reason for this situation is that almost all of the teachers serving in the city of >yrnak are reappointed away from this region before they complete their fifth year. As for the reasons why teachers do not stay in the region for more than five years, it was found that safety of life is their main concern.